Hydrothermal synthesis, crystal structure and properties of a two‐dimensional uranyl coordination polymer based on a flexible zwitterionic ligand. Issue 3 (27th February 2018) - Cui, Wen; Wang, Ruyu; Shu, Xi; Fan, Yu; Liu, Yang; Jin, Yongdong; Xia, Chuanqin; Huang, Chao
Abstract : The hydrothermal reaction of various uranyl compounds with flexible zwitterionic 1, 1′‐[1, 4‐phenylenebis(methylene)]bis(pyridin‐1‐ium‐4‐carboxylate) dihydrochloride resulted in the formation of a novel two‐dimensional uranyl coordination polymer, which exhibits a layered arrangement with the (UO2 ) 2+ centre coordinated by five equatorial O atoms. Abstract : The interaction between the uranyl cation, (UO2 ) 2+, and organic species is of interest due to the potential applications of the resulting compounds with regard to nuclear waste disposal and nuclear fuel reprocessing. The hydrothermal reaction of various uranyl compounds with flexible zwitterionic 1, 1′‐[1, 4‐phenylenebis(methylene)]bis(pyridin‐1‐ium‐4‐carboxylate) dihydrochloride (Bpmb·2HCl) in deionized water containing drops of H2 SO4 resulted in the formation of a novel two‐dimensional uranyl coordination polymer, namely poly[tetraoxidoμ2 ‐1, 1′‐[1, 4‐phenylenebis(methylene)]bis(pyridin‐1‐ium‐4‐carboxylate)di‐μ3 ‐sulfato‐diuranium(VI)], [(UO2 )2 (SO4 )2 (C20 H16 N2 O4 )] n, (1). Single‐crystal X‐ray diffraction reveals that this coordination polymer exhibits a layered arrangement and the (UO2 ) 2+ centre is coordinated by five equatorial O atoms. The structure was further characterized by FT–IR spectroscopy, powder X‐ray diffraction (PXRD) and thermogravimetric analysis (TGA). The polymer shows high thermal stability up to 696 K. Furthermore, the photoluminescence properties of (1) has also been studied, showing it to exhibit a typical uranyl fluorescence.